EFEKTIVITAS LATIHAN CIRCUIT TRAINING TERHADAP PENINGKATAN KARDIOVASKULAR PADA EKSTRAKURIKULER FUTSAL DI SD NEGERI SIEM - Billy Zurihan; Zikrur Rahmat; Mahmudin Aritanoga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Physical education plays an important role in improving students’ physical fitness, particularly cardiovascular endurance, which is essential in sports activities such as futsal. One method that can be applied is circuit training, which effectively trains heart and lung endurance. This study aimed to determine the level of students’ cardiovascular ability before being given circuit training and to examine the effectiveness of circuit training in improving students’ cardiovascular endurance. This research employed a quantitative approach with a One Group Pretest-Posttest Design. The sample consisted of 20 students. The instrument used was a fitness test to measure cardiovascular ability (VO₂max). Data analysis was conducted using the Shapiro-Wilk normality test and hypothesis testing using a paired sample t-test. The results showed that the data were normally distributed, with significance values of 0.759 for the pretest and 0.648 for the posttest (p > 0.05). The t-test results indicated a significance value of 0.000 (p < 0.05) with a t-value of -32.023, meaning there was a significant difference between pretest and posttest results. The findings suggest that the improvement occurred because circuit training was implemented in a structured, repetitive manner and involved various movements that enhanced heart and lung performance. Additionally, the variation in exercises increased students’ motivation and participation. In conclusion, circuit training is effective in improving the cardiovascular endurance of students participating in futsal extracurricular activities at SD Negeri Siem. Therefore, it is recommended that teachers or coaches apply this method regularly, students participate consistently, and schools provide adequate sports facilities to support students’ physical fitness improvement